2021
DOI: 10.3390/polym13091428
|View full text |Cite
|
Sign up to set email alerts
|

Application of Furcellaran Nanocomposite Film as Packaging of Cheese

Abstract: There is a serious need to develop and test new biodegradable packaging which could at least partially replace petroleum-based materials. Therefore, the objective of this work was to examine the influence of the recently developed furcellaran nanocomposite film with silver nanoparticles (obtained by an in situ method) on the quality properties of two cheese varieties: a rennet-curd (gouda) and an acid-curd (quark) cheese. The water content, physicochemical properties, microbiological and organoleptic quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Several phytochemicals with antimicrobial properties have been reported to be present in E. purpurea extract with proven antimicrobial activity against microbes such as Mycobacterium smegmatis, Streptococcus pyogenes, E. coli, Bacillus subtilis, Staphylococcus aureus , Pseudomonas aeruginosa, and Enterococcus faecalis [12] . Several studies, such as Pluta-Kubica et al [40] , Olaimat et al [41] and Chen et al [42] , have reported a significant decrease in spoilage and pathogenic microbial counts during storage for the food samples, such as cheese, packaged within the edible films containing nanoparticles as bioactive agents.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Several phytochemicals with antimicrobial properties have been reported to be present in E. purpurea extract with proven antimicrobial activity against microbes such as Mycobacterium smegmatis, Streptococcus pyogenes, E. coli, Bacillus subtilis, Staphylococcus aureus , Pseudomonas aeruginosa, and Enterococcus faecalis [12] . Several studies, such as Pluta-Kubica et al [40] , Olaimat et al [41] and Chen et al [42] , have reported a significant decrease in spoilage and pathogenic microbial counts during storage for the food samples, such as cheese, packaged within the edible films containing nanoparticles as bioactive agents.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Two cheese varieties, a rennet-curd (gouda) and an acid-curd (quark) cheese, were tested with the addition of furcellaran nanocomposite film with silver nanoparticles by Pluta-Kubica et al [ 90 ]. The cheese quality was examined, indicating that the use of the film improved the microbiological quality of cheeses during storage, slowing down and inhibiting the growth of yeast in gouda and quark, respectively.…”
Section: Nanostructured Antimicrobials In Dairy Industrymentioning
confidence: 99%
“…The resulted color differences could be partly determined also by the different WVTR values characterizing the three cling films, since the NR-BP film has higher WVTR values than the films made from renewable and circular resources, R-BP1 and R-BP2. In fact, higher water vapor permeability may affect shelf life and may lead to a variation in food quality, thus influencing weight loss and color variation [37]. In the case of cheese, a w is responsible for its stability.…”
Section: Effect Of the Cling Films On Cheese Color Over Storage Timementioning
confidence: 99%
“…In fact, cheese packaged with the R-BP1 cling film was more appreciated in terms of odor by the participants than cheese packaged with the others cling films, except for R-BP2. That is the case of the work of Pluta-Kubica et al [37], in which the odor of the cheese wrapped in the active biodegradable film was less appreciated by the panelists than that of the control, possibly as a consequence of the decrease in water content following a much higher WVTR of the biodegradable film. Amjadi et al [48] also observed lower hedonic odor scores and overall acceptance during storage of white cheese wrapped in biodegradable films containing zinc oxide nanoparticles.…”
Section: Variablesmentioning
confidence: 99%